2004
DOI: 10.1063/1.1686903
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porosity on the electrical properties of Y2O3-doped SrTiO3 internal boundary layer capacitors

Abstract: Articles you may be interested inLow dielectric loss, dielectric response, and conduction behavior in Na-doped Y2/3Cu3Ti4O12 ceramics The sintering temperature effects on the electrical and dielectric properties of Li 0.05 Ti 0.02 Ni 0.93 O ceramics prepared by a direct thermal decomposition method Compositions of 0.8 mole % Y 2 O 3 -doped SrTiO 3 were sintered over a range of temperatures of 1450-1550°C for times of 1-15 h, and the resulting internal boundary layer capacitors had relative densities ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…However, the effect of porosity on the dielectric conductivity needs further investigation. In semiconducting SrTiO 3 doped with Y 2 O 3 , it is reported that increase in porosity has resulted in decrease in conductivity [19]. However, in polycrystalline NaNbO 3 ceramic, porous counterpart is known to exhibit higher bulk conductivity than dense ones [20].…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 99%
“…However, the effect of porosity on the dielectric conductivity needs further investigation. In semiconducting SrTiO 3 doped with Y 2 O 3 , it is reported that increase in porosity has resulted in decrease in conductivity [19]. However, in polycrystalline NaNbO 3 ceramic, porous counterpart is known to exhibit higher bulk conductivity than dense ones [20].…”
Section: Electrical Conductivity Measurementsmentioning
confidence: 99%
“…One is the grain size and its uniformity. Many investigations show that larger grain size and higher uniformity are helpful to the increasing of Q × f value [ [17] , [18] , [19] , [20] , [21] ]. Another is the impure phase.…”
Section: Resultsmentioning
confidence: 99%
“…The primary factor affecting grain size was identified as the melting behavior of the Y 2 O 3 powder particles. The better the melting effect, the smaller the porosity of the coating, and some studies have found that there was a high correlation between the effective permittivity and the effective conductivity, and, with the increase in porosity, both the dielectric constant and the effective conductivity decreased strongly [20]. According to the Scherrer equation, the grain size (d) and grain size of the coating were calculated [21,22] as follows:…”
Section: Analysis Of Pore Typesmentioning
confidence: 99%